News as authentic materials to improve essay writing in a hybrid learning setting - Lestari Setyowati; Sony Sukmawan (Studies in English Language and Education, 2021)
This study aimed to investigate the effect of using news as authentic materials for essay writing skills. This experimental study employed the one-group pre-test and post-test design to 18  fourth-semester students who joined the Essay Writing Course in one of the universities in Indonesia. These students were selected through systematic random sampling and went through treatments for 12 meetings where they were taught in a hybrid learning setting. The first four meetings used the conventional face-to-face classroom interaction. The rest of the meetings were done online because of the outbreak of COVID 19. The instruments to collect data were tests and documentation. Before they were given to the students, the teaching materials, pre-test, and post-test designs were tested and validated. The authentic materials were news texts about global issues such as poverty, environmental protection, gender, race and ethnicities, and diseases. Two raters scored the students’ writing by using Jacobs ESL Composition Profile. The researchers used IBM SPSS 25 software to analyze the data. The results of a paired sample t-test analysis showed that there was no significant difference in the students’ writing scores before and after using news as authentic materials (p = .959 α = 0.05). The paper further discusses the implications of this study for theoretical and practical use.